'The age-old struggle': Irish republicanism from the Battle of the Bogside to the Belfast Agreement, 1969-1998 - Hepworth, Jack (Liverpool University Press, 2024)
This is a wide-ranging analysis of the internal dynamics of Irish republicanism between the outbreak of ‘the Troubles’ in 1969 and the Good Friday Agreement of 1998. Engaging a vast array of hitherto unused primary sources alongside original and re-used oral history interviews, this book draws upon the words and writings of more than 250 Irish republicans. This book scrutinises the movement's historical and contemporary complexity, the variety of influences within Irish republicanism, and divergent republican responses at pivotal moments in the conflict. Yet it also assesses the centripetal forces which connected republican organisations through decades of struggle.